Vascular endothelial growth factor A: friend or foe in the pathogenesis of HIV and SARS-CoV-2 infections? - van der Mescht, Mieke A.; Steel, Helen C.; Anderson, Ronald; Rossouw, Theresa M. (Frontiers in Cellular and Infection Microbiology, 2025)
This review article discusses the role of vascular endothelial growth factor A (VEGF-A) in the pathogenesis of SARS-CoV-2 and HIV infection, both conditions being renowned for their impact on the vascular endothelium. The processes involved in vascular homeostasis and angiogenesis are reviewed briefly before exploring the interplay between hypoxia, VEGF-A, neuropilin-1 (NRP-1), and inflammatory pathways. We then focus on SARS-CoV-2 infection and show how the binding of the viral pathogen to the angiotensin-converting enzyme 2 receptor, as well as to NRP-1, leads to elevated levels of VEGF-A and consequences such as coagulation, vascular dysfunction, and inflammation. HIV infection augments angiogenesis via several mechanisms, most prominently, by the trans-activator of transcription (tat) protein mimicking VEGF-A by binding to its receptor, VEGFR-2, as well as upregulation of NRP-1, which enhances the interaction between VEGF-A and VEGFR-2. We propose that the elevated levels of VEGF-A observed during HIV/SARS-CoV-2 co-infection originate predominantly from activated immune cells due to the upregulation of HIF-1α by damaged endothelial cells. In this context, a few clinical trials have described a diminished requirement for oxygen therapy during anti-VEGF treatment of SARS-CoV-2 infection. The currently available anti-VEGF therapy strategies target the binding of VEGF-A to both VEGFR-1 and VEGFR-2. The blocking of both receptors could, however, lead to a negative outcome, inhibiting not only pathological, but also physiological angiogenesis. Based on the examination of published studies, this review suggests that treatment targeting selective inhibition of VEGFR-1 may be beneficial in the context of SARS-CoV-2 infection.